The Use of Tissue Engineering to Fabricate Perfusable 3D Brain Microvessels in vitro - Galpayage Dona, Kalpani N. Udeni; Hale, Jonathan Franklin; Salako, Tobi; Anandanatarajan, Akanksha; Tran, Kiet A.; DeOre, Brandon J.; Galie, Peter Adam; Ramirez, Servio Heybert; Andrews, Allison Michelle (Frontiers in Physiology, 2021)
Tissue engineering of the blood-brain barrier (BBB) in vitro has been rapidly expanding to address the challenges of mimicking the native structure and function of the BBB. Most of these models utilize 2D conventional microfluidic techniques. However, 3D microvascular models offer the potential to more closely recapitulate the cytoarchitecture and multicellular arrangement of in vivo microvasculature, and also can recreate branching and network topologies of the vascular bed. In this perspective, we discuss current 3D brain microvessel modeling techniques including templating, printing, and self-assembling capillary networks. Furthermore, we address the use of biological matrices and fluid dynamics. Finally, key challenges are identified along with future directions that will improve development of next generation of brain microvasculature models.